Analysis of Hematological and Biochemical Parameters in Rheumatoid Arthritis Patients from Faisalabad, Punjab: Hematological and Biochemical Parameters in Rheumatoid Arthritis Patients - Raza, Syed Kashif; Ahmad, Rizwan; Wahla, Faisal Murtaza; Majid, Usama Bin; Areeb, Muhammad; Rehman, Abdul (Pakistan Journal of Health Sciences, 2025)
Rheumatoid Arthritis (RA) is a long-term autoimmune disease that causes inflammation and joint degeneration. It can lead to significant impairment and a loss in quality of life for millions of people worldwide. When diagnosing and treating RA, hematological and biochemical indicators are frequently assessed. These data are essential for monitoring the disease’s progression, identifying organ involvement, and making treatment decisions. Objectives: To come up with some significant differences in hematological and biochemical indicators between patients with RA and healthy controls for the diagnosis of RA. Methods: Three hundred blood samples were taken in total from the population of Faisalabad City; 150 blood samples were drawn from people who have been confirmed diagnosed with RA, and 150 blood samples were collected from healthy people without any disease. The significant levels between the two groups were ascertained by calculating descriptive statistics and statistical comparisons using independent t-tests for continuous variables. Results: Among assessed parameters, erythrocyte sedimentation rate (ESR) and white blood cells (WBCs) were hematological parameters found to be highly elevated in RA patients, whereas hemoglobin (Hb) and alkaline phosphatase (ALP) are biochemical parameters that have been demonstrated significantly low in RA patients as compared to healthy. Conclusions: Deferentially expressed parameters ESR, WBCs, Hb, and ALP can be used for the diagnosis of RA.